Explore the Carpathian Garden A Multimodal Nation Branding Campaign Analysis - Mustata, Oana Roxana (My University, 2013)
So far, all Romanian nation branding campaigns have been criticized for not showing the country’s unique attributes and not painting a clear picture of its country image. Explore the Carpathian Garden is the latest Romanian endeavor into nation branding. This paper utilizes a multimodal semiotic analysis in order to provide insight into the way the Romanian country image is constructed in the latest campaign. The paper’s hypothesis is that the problematic aspects of the previous campaigns are still present in Explore the Carpathian Garden. This thesis analyzes the construction of Romania’s country image in the campaign, in order to uncover these problematic aspects, which can lead to confusion on the part of the viewer and perhaps even undermine the campaign’s efforts.
Keywords: nation branding; advertising; tourism; national image; semiotics; multimodality; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|